The idealism of freedom for a hegelian turn in philosophy - Vieweg, Klaus 1953- (Critical studies in German idealism, 2020)
"This volume brings together essays on Hegel from various decades of my involvement with the most important philosophical thinker of modernity. It is directed against some of the misinterpretations, malicious legends, and fairy tales about Hegel that are still prevalent today"--